The effect of training through the principle of individualization and the principle of play on the dribbling ability of football school players porma aged 10-13 - Yudha Ilhajri Anwar; Ronni Yenes; Emral Emral; Alex Aldha Yudi (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
This study aims to determine the effect of dribbling training through the principle of individualization on the dribbling ability of football school players (SSB). This type of study is a quasi-experiment. Design This study used a